Les femmes, l’environnement et le développement durable - Braidotti, Rosi; Charkiewicz, Ewa; Häusler, Sabine; Wieringa, Saskia (Genre, mouvements populaires urbains et environnement, 2007)
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; discours dominant; environnement; histoire et politique; inégalités; patriarcat; projet charge mentale; périodes historiques; racisme; ressource en ligne; santé; systèmes d'oppressions; thématiques; écoféminisme

Fonction sexuelle masculine et sexualité féminine - Giami, Alain (Communications, 2007)
Major changes have occurred in male and female sexual function/dysfunction research and treatments. Male erectile dysfunction has been re-conceptualized as an organic dysfunction, which marks a dramatic shift from previous conceptions of psychogenic impotence developed during the 60' and the 70's. This shift is based on major scientific discoveries, and pharmacological advances that took place since the early 80's under the influence of North American urologists. The release of sildenafil in 1998 was thecorner stone of a new paradigm of treatments focusing on male penile activity, far remote from any psychological approaches. More recently, the same group of urologists started to reconsider Female Sexual Dysfunction using the same organic/biological model of sexual function. New pharmaceutical products are currently under trial for the treatment of this new category of female sexual disorder. But as opposed to the absence of public adverse reaction to the development of this approach of male function, many voices raised to oppose this new conception of female function. A major discussion took place in the British Medical Journal (2003) stating that female sexual function was not organically driven, but rather determined by the social, psychological and interpersonal context of female sexual activity and relations. One of the major dimension of this discussion opposed the so-called "simplicity" of male sexual function to the "complexity" of female sexual function.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 2000 à aujourd'hui; 2000-2009; angleterre; approches et analyses; cours; discipline; essentialisme; europe; féminisme radical; patriarcat; premier cycle; pédagogie; périodes historiques; recherche; régions géographiques; santé; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

Transcultural bodies: female genital cutting in global context - Hernlund, Ylva; Shell-Duncan, Bettina (Rutgers University Press, 2007)
Female "circumcision" or, more precisely, female genital cutting (FGC), remains an important cultural practice in many African countries, often serving as a coming-of-age ritual. It is also a practice that has generated international dispute and continues to be at the center of debates over women's rights, the limits of cultural pluralism, the balance of power between local cultures, international human rights, and feminist activism. In our increasingly globalized world, these practices have also begun immigrating to other nations, where transnational complexities vex debates about how to resolve the issue. Bringing together thirteen essays,Transcultural Bodiesprovides an ethnographically rich exploration of FGC among African diasporas in the United Kingdom, Europe, and Australia. Contributors analyze changes in ideologies of gender and sexuality in immigrant communities, the frequent marginalization of African women's voices in debates over FGC, and controversies over legislation restricting the practice in immigrant populations.
Keywords: afrique; anthropologie; approches et analyses; australie; corps; cours; discipline; europe; histoire et politique; océanie; premier cycle; racisme; ressource en ligne; royaume-uni; régions géographiques; santé; sciences humaines; sex2283; sexisme; sexualité; sociologie; système colonial; systèmes d'oppressions; thématiques; transculturalisme; violences